The efficacy of flubendiamide and chlorantraniliprole and silica nano particles against of the tomato leaf miner Tuta absoluta (Meyrick ) under greenhouse conditions - طباش, سمير; قره علي, أحمد; أحمد, محمد; الحايك, ريتا (Latakia University Journal -Biological Sciences Series, 2020)
The efficacy of flubendiamide, chlorantraniliprole and nanosilica particles was tested against Tuta absoluta under plastic house conditions where both pesticides were used at the recommended concentrations (0.4 g / l and 0.31 ml / l) and nanosilica at ppm500. The results showed significant differences between all treatments and control in terms of the number of live larvae / plants. The efficacy of flubendiamide and chlorantraniliprole was 51.37 and. 63.85% after 7 days of the first spray and reached 52.33 and 69.95 after 7 days of the second spray, respectively. Efficacy of nanosilica particles has ranged from 36.14 to 55.15, respectively. All treatments reduced the number of infested fruits with a significant difference with the control, where the reduction was 63.83% for flubendiamide treatment, 64.62% for chlorantraniliprole and 37.11% for nanosilica particles on the tenth day after the first spray and reached 37.5, 58.7 and 34.81% respectively. 9 days from the second spray. The results showed the efficacy of flubendiamide, chlorantraniliprole and nanosilica particles in reducing the severity of the infection on fruits and reached 40, 26.3 and 23.2%, respectively after 10 days of the first spray compared to the control and reached 51.8, 76.8 and 42.4% after 9 days. of the second spray, compared to the control. There were significant differences between chlorantraniliprole and all the rest of the treatments.